Managing patients undergoing non-cardiac surgery: need to shift emphasis from risk stratification to risk modification. Issue 1 (19th December 2005) - Karthikeyan, G; Bhargava, B
Abstract : Many patients undergo non-invasive testing for the detection of coronary artery disease before non-cardiac surgery. This is despite the low predictive value of positive tests in this population and the lack of any evidence of benefit of coronary revascularisation before non-cardiac surgical procedures. Further, this strategy often triggers a clinical cascade exposing the patient to progressively riskier testing and intervention and results in increased costs and unnecessary delays. On the other hand, administration of β blockers, and more recently statins, has been shown to reduce the occurrence of perioperative ischaemic events. Therefore, there is a need for a shift in emphasis from risk stratification by non-invasive testing to risk modification by the application of interventions, which prevent perioperative ischaemia—principally, perioperative β adrenergic blockade and perhaps treatment with statins. Clinical risk stratification tools reliably identify patients at high risk of perioperative ischaemic events and can guide in the appropriate use of perioperative medical treatment.